2008
DOI: 10.5751/es-02489-130133
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Ecological Resilience of Drylands Using Digital Remote Sensing

Abstract: ABSTRACT. Drylands cover 41% of the terrestrial surface and support > 36% of the world's population. However, the magnitude of dryland degradation is unknown at regional and global spatial scales and at 15-30-yr temporal scales. Historical archives of > 30 yr of Landsat satellite imagery exist and allow local to global monitoring and assessment of a landscape's natural resources in response to climatic events and human activities. Vegetation indices (VIs), i.e., proxies of vegetation characteristics such as ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 49 publications
0
52
2
1
Order By: Relevance
“…There is concern that eutrophication and water level changes will influence patterns of structure and processes in shallow lakes [3][4][5]. However, our results, together with findings from previous research [34,77], suggest that unless persistent dry spells caused by a state shift in meteorological and climatological settings on a regional scale, resilience attributes of shallow lakes may be otherwise little affected by changing water levels or trophic state conditions at least within our studied range. In practice, this means that drought mitigation and natural resource management might be especially challenging in arid and semi-arid countries in the future, because as our study suggests, these effects can be spatially contingent and difficult to predict [70,71,87].…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…There is concern that eutrophication and water level changes will influence patterns of structure and processes in shallow lakes [3][4][5]. However, our results, together with findings from previous research [34,77], suggest that unless persistent dry spells caused by a state shift in meteorological and climatological settings on a regional scale, resilience attributes of shallow lakes may be otherwise little affected by changing water levels or trophic state conditions at least within our studied range. In practice, this means that drought mitigation and natural resource management might be especially challenging in arid and semi-arid countries in the future, because as our study suggests, these effects can be spatially contingent and difficult to predict [70,71,87].…”
Section: Discussioncontrasting
confidence: 41%
“…This is at odds with the expectation that communities operate in a single broad basin of attraction and also with the finding that the Turkish zooplankton did not undergo such a shift, despite having suffered drawdown. However, Angeler et al [34] and Washington-Allen et al [77] found that severe drought events over prolonged periods of time (i.e., supra-seasonal droughts), a consequence of climate change [78,79] especially in arid countries [80], trigger nonlinear state shifts in hydrological functioning and biological communities. Such changes have also been documented in other studies [81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…Bofedales provide vital dry season grazing, and increased bofedal vegetation due to check dams can contribute to grazing stability (Preston et al 2002;Washington-Allen et al 2008). The increased standing water associated with check dams also has implications for water security in arid and semiarid lands (Scott et al 2013), contributing to groundwater recharge and stabilization of downstream water flows (Bouwer 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Bofedales are particularly sensitive to changes in hydrology induced by gully erosion or prolonged drought (Earle et al 2003;Moreau & Toan 2003;Squeo et al 2006;Washington-Allen et al 2008). Bofedal degradation impacts local livelihoods, as they are a vital source of dry season grazing for llamas and sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Informed by work by Pickup and Foran [34] and more recent work [35][36][37][38], we used mean-variance analysis, a form of graphical dynamical systems analysis previously used successfully in dry land ecosystems with remotely-sensed data. Mean-variance analyses are based on established empirical relationships that show that the location of statistical vegetation parameters such as mean and variance in a Cartesian space can be correlated to field measurements of vegetation heterogeneity, homogeneity and overall vegetation productivity.…”
Section: Introductionmentioning
confidence: 99%